The Comparison of Shotput Techniques in Junior High School: O’Brien Style vs Spin Style - Akhmad Sobarna; Mochamad Ishak; Asep Rahmat; Ahmad Afandi Harja (STAI Hubbulwathan Duri, 2022)
This research aims to compare the shotput technique between the O’Brien style and the spin style. This study uses comparative causal research. The population in this study is 150 junior high school students in Belitung. Through purposive sampling techniques obtained samples, namely the sample in this study is class VIII which amounts 15 students. The research design used is quantitative, which utilized the result of posttest after completing the learning. The initial analysis used hypotheses with the help of the SPSS24 (Statistical Product and Service Solution) computer program. The researcher's hypothesis test uses the t-test (independent sample t-test). Based on the SPSS output, the t-test (independent sample t-test) with a significant level of 0.04 with a specified lower limit of 0.05 obtained t calculated = 2.134 and t table = 2.0484. The H0 acceptance area is if t calculates 2.0484, it is clear that H0 is rejected. Thus, it can be concluded that there is a comparison between O'Brien style and Spin style, in which O’Brien Style gives the best results in learning shotput to students from junior high school students in the research field.